Nanostructure photovoltaics based on III-V compound semiconductors - Fu, L; Lu, H; Lee, J; Li, Z; Turner, S; Parkinson, P; Breuer, S; Jolley, G; Mokkapati, S; Tan, H; Jagadish, C (2013)
In this work, solar cells based on III-V compound semiconductor quantum dots and nanowires are demonstrated. Experimental results based on material and device studies will be presented and discussed for high efficiency photovoltaic applications. © OSA 2013.